2011
DOI: 10.1155/2011/419809
|View full text |Cite
|
Sign up to set email alerts
|

Novel Conjugates of 1,3-Diacylglycerol and Lipoic Acid: Synthesis, DPPH Assay, and RP-LC-MS-APCI Analysis

Abstract: 1,3-Diacylglycerol is known to reduce body weight and fat deposits in humans. α-Lipoic acid is a potent antioxidant and effective against many pathological conditions, including obesity and related metabolic syndromes. The present work is based on the hypothesis that the hybrid molecules of 1,3-diacylglycerol and lipoic acid possess synergistic and/or additive effects compared with the parent compounds against obesity, overweight, and related metabolic syndromes. Laboratory scale synthesis of 1,3-dioleoyl-2-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
(54 reference statements)
5
10
1
2
Order By: Relevance
“…• in this study is in agreement as it was observed in LA derivatives of 1,3-diolein [Madawala et al, 2011]. In a previous study, LA and several coumarin derivatives of LA dissolved in ethanol at 0.5 mmol/L concentration of the fi nal mixture measured after 20 and 60 min have also • dependent on concentration.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…• in this study is in agreement as it was observed in LA derivatives of 1,3-diolein [Madawala et al, 2011]. In a previous study, LA and several coumarin derivatives of LA dissolved in ethanol at 0.5 mmol/L concentration of the fi nal mixture measured after 20 and 60 min have also • dependent on concentration.…”
Section: Discussionsupporting
confidence: 90%
“…Mass spectra recorded in negative mode for all individual PSLA derivatives, showed the dominant fragment ion at m/z 205, derived from the LA moiety dissociated at the esterifi ed position. A fragment ion at m/z 171 correspond to a loss at m/z 34, due to the elimination of H 2 S from m/z 205 fragment concur with the previously published report [Schupke et al, 2001;Madawala et al, 2011].…”
Section: H]supporting
confidence: 92%
See 3 more Smart Citations